THE IMPACT OF ISLAMIC FINANCING ON THE OPERATIONS OF SMES IN OMAN - Kiran, Faiza (International Journal of Islamic Banking and Finance Research, 2022)
The study investigates the relationship between the growth of Islamic banks & financial institutions and the operational performance of small and medium enterprises located in Oman. The study employs qualitative method for data gathering. An effective questionnaire was created to gather the opinions of participants through semi-structured interviews. The sample consist of 40 employees of SMEs, 20 managers, and 2 financial experts. Thematic and descriptive analysis was used for analyzing data. Research findings revealed that owners/managers of SMEs and employees have effective knowledge regarding Islamic financing principles. Although the Islamic financing strategy is new in Oman, most participants including financial experts showed positive interest regarding its adaption. Further, findings indicated that there is a positive correlation between operations of Omani SMEs and Islamic financing. It is found that Islamic financing has benefitted SME operations as well as could play a significant role in the growth of SMEs and their operations in the future. This study helps policymakers and banks in understanding the scope of the growth in future. Thus, these banks can attract more SMEs and improve their growth rate. Finally, a comprehensive perception regarding workers, SME owners, and financial experts clarify willingness of using Islamic financing to get potential benefits in operations. JEL Classification Codes: F65, D02.